Reinforced aneurysmorrhaphy for true aneurysmal haemodialysis vascular access - Rokošný, S; Baláž, P; Wohlfahrt, P; Palouš, D; Janoušek, L (European journal of vascular and endovascular surgery, 2014)
OBJECTIVE: In 2008, a new technique of reinforced aneurysmorrhaphy with a polyester mesh tube for salvaging true aneurysmal arteriovenous (AV) haemodialysis access was described by us. In this study, the long-term patency and complication rates associated with this procedure were analysed, and the effect of reinforced aneurysmorrhaphy on high-flow vascular access was assessed. METHODS: This was a retrospective non-randomised study with prospectively collected data performed at a single centre. Patients with true aneurysmal haemodialysis AV access who underwent aneurysmorrhaphy with external mesh prosthesis between March 2007 and October 2012 were included. Clinical assessment and duplex ultrasound were performed preoperatively, 1, 3, and 12 months postoperatively, and annually thereafter. RESULTS: Data from 62 patients (median age 60 years, range 28-81 years; 63% men) were analysed. The commonest indication was high-flow vascular access associated with the risk of high output cardiac failure (24 patients, 39%). The mean follow-up time was 14.66 ± 12.80 months. Primary patency rates at 6 and 12 months were 86% and 79% respectively. Assisted primary patency rates at 6 and 12 months were 89% and 80% respectively. In 23 patients (96%) operated on for high-flow vascular access, decreased vascular access flow was observed after the procedure. The average flow reduction after aneurysmorrhaphy was 2,197 mL/minute. Postoperative bleeding and infection necessitating surgical revision occurred in three (4.8%) and three (4.8%) patients respectively. CONCLUSIONS: Reinforced aneurysmorrhaphy with an external mesh prosthesis is an effective method for treating true aneurysmal haemodialysis AV access, with excellent long-term patency and minimal complications due to infection.
Keywords: dospělí; Aneurysmorrhaphy; aneurysma; Female; External mesh prosthesis; Renal Dialysis; dialýza ledvin; Adult; výkony cévní chirurgie; cévy - implantace protéz; výsledek terapie; ženské pohlaví; Aneurysm; průchodnost cév; lidé; Treatment Outcome; Aged, 80 and over; Graft Occlusion, Vascular; Vascular Surgical Procedures; Reoperation; reoperace; retrospektivní studie; High-flow access; Arteriovenous access; Male; Aged; Vascular Patency; okluze cévního štěpu; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Blood Vessel Prosthesis Implantation; Retrospective Studies; Middle Aged; Humans